Fish Symbol and Maritime Motifs on Late Antique Lamps from Central Balkans - Tešić Radovanović, Danijela T. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Elements of Christian visual culture appeared in various media in monumental and applied art during the late antique period, from painted decoration in the catacombs, through funerary monuments, to utilitarian objects such as jewellery and lamps. The paper analyses the symbolic meaning of fish and maritime motifs in the context of the late antique visual culture of the Mediterranean and their meaning within the Interpretatio Christiana, as well as the appearance of these motifs on late antique lamps. Ten lamps with maritime motifs or in the form of fish or dolphins are known from the territory of the Central Balkans. Elements of decoration are considered in relation to analogies, textual references, and the context of the finds.
Keywords: lamp; light; fish; shell; ship; maritime motifs; iconography